2020
DOI: 10.1097/cce.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Propofol-Induced Hypertriglyceridemia and Identification of Associated Risk Factors

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…A recent study at the same institution found that 27.9% of patients developed triglyceride concentrations ≥400 mg/dL while on propofol, with a 1.5% incidence of acute pancreatitis. 10 In this study, patients developed hypertriglyceridemia after a median of 47 hours (IQR, 16.3-73.5 hours) and received a median cumulative propofol dose of 21 800 mg (IQR, 9300-32 400 mg). This contrasts with our study because patients developed hypertriglyceridemia after a median of 3.8 days and received a median cumulative propofol dose of 11 700 mg in our cohort.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A recent study at the same institution found that 27.9% of patients developed triglyceride concentrations ≥400 mg/dL while on propofol, with a 1.5% incidence of acute pancreatitis. 10 In this study, patients developed hypertriglyceridemia after a median of 47 hours (IQR, 16.3-73.5 hours) and received a median cumulative propofol dose of 21 800 mg (IQR, 9300-32 400 mg). This contrasts with our study because patients developed hypertriglyceridemia after a median of 3.8 days and received a median cumulative propofol dose of 11 700 mg in our cohort.…”
Section: Discussionmentioning
confidence: 91%
“…Our study supports previously published evidence that propofol-associated acute pancreatitis is rare. [8][9][10] However, in response to hypertriglyceridemia, providers in our study often lowered the dose or discontinued propofol altogether and added or transitioned to an alternative sedative, often a benzodiazepine, to facilitate propofol weaning. Guidelines recommend minimizing benzodiazepines to improve shortterm outcomes such as risk of delirium and shorten the duration of mechanical ventilation and ICU length of stay.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, unlike HDL-C and LDL-C concentrations, the level of TG remained approximately the same over time in our study. A possible explanation is that the prolonged systematic use of propofol, which thus increases the plasma triglyceride concentrations 34 , may be counterbalanced by the systematic use of unfractionated heparin. Indeed, unfractionated heparin leads to an increased synthesis of lipoprotein lipase, which increases the hydrolysis of TG from plasma lipoproteins such as very low density lipoproteins or chylomicrons 35 .…”
Section: Discussionmentioning
confidence: 99%